Influences of solid and lubricant thermal conductivity on traction in an EHL circular contact. (June 2020) - Liu, H.C.; Zhang, B.B.; Bader, N.; Poll, G.; Venner, C.H.
Abstract: The influences of thermal conductivity of both the contacting solids and the lubricant on the traction in a rolling/sliding EHL contact have been studied numerically. For through-hardened AISI 52100 bearing steel ( k was measured as 21 W / mK by Reddyhoff et al. see Tribol Lett 67 ( 1 ) : 22, 2019 ), with the improper but widely used thermal conductivity of 46 W / mK in literature, the friction coefficient can be overestimated and the maximum temperature in the lubricating film would be underestimated. The effect of solid thermal conductivity on traction depends on the entrainment speed and the resulting film thickness. For the thermal conductivity of the lubricant, its pressure dependence affects the traction mainly at high speeds and/or at high sliding-to-rolling ratio (SRR) conditions. Highlights: The widely cited thermal conductivity value of hardened AISI-52100 steel may be wrong. The specimens of traction machine are usually made of through-hardened 52100 steel. A thermal EHL model was built for reference liquids with physically-sound fluid models. k solid and k oil affect temperature rise and traction prediction, but in two different ways. The effect of solid thermal conductivity on traction depends on speed and film thickness.